Optical coherence tomography-guided vs. intravascular ultrasound-guided percutaneous coronary intervention: a systematic review and meta-analysis of randomized controlled trials - Vats, Vaibhav; Elahi, Aarij; Hidri, Sinda; Abdelkader, Rem Ehab; Munaf, Farhan; Prince, Jennifer Mercika; Asif, Muhammad Ahsan; Cheema, Huzaifa Ahmad; Ahmad, Adeel; Rehman, Wajeeh Ur; Nashwan, Abdulqadir J.; Ahmed, Raheel; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Optical coherence tomography (OCT) and intravascular ultrasound (IVUS) are superior to coronary angiography for guiding percutaneous coronary intervention (PCI). However, whether one technique is superior to the other is inconclusive.We searched PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov from inception to November 2023 for randomized controlled trials (RCTs) comparing OCT and IVUS in patients undergoing PCI. RevMan 5.4 was used to pool outcomes with risk ratio (RR) as the effect measure.Results: Six RCTs (4402 patients) were included in this meta-analysis. There was no significant difference between the OCT-and IVUS-guided PCI groups in the risk of major adverse cardiovascular events (RR 0.87, 95% CI: 0.65, 1.16; I 2 =0%) and cardiac mortality (RR 0.73, 95% CI: 0.24, 2.21; I 2 =0%). The results were consistent across the subgroups of the presence or absence of left main disease (P interaction > 0.1). There were no significant differences between OCT and IVUS in the risk of target lesion revascularization (RR 0.78, 95% CI: 0.47, 1.30; I 2 =0%), target vessel revascularization (RR 1.06, 95% CI: 0.69, 1.62; I 2 =0%), target-vessel myocardial infarction (RR 0.79, 95% CI: 0.40, 1.53; I 2 =0%), stent thrombosis (RR 0.59, 95% CI: 0.12, 2.97; I 2 =0%), and all-cause mortality (RR 1.01, 95% CI: 0.53, 1.90; I 2 =0%).Our meta-analysis demonstrated similar clinical outcomes in OCT-and IVUSguided PCI. New large-scale multicenter RCTs with long-term follow-up are required to confirm or refute our findings and provide more reliable results.